Solid polymer electrolytes based on chitosan and dy(CF3SO3)3 for electrochromic devices - Alves, Raquel Diana Carneiro (2017)
In the present work, one host natural matrix (chitosan) was doped with glycerol and different amounts of dysprosium triflate salt (Dy(CF3SO3)3). The behaviour of the electrolytes was evaluated by thermal analyses (thermogravimetric analysis – TGA and differential scanning calorimetry – DSC), impedance spectroscopy, X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), and atomic force microscopy (AFM). Sample with 0.15 g of Dy(CF3SO3)3 showed the best ionic conductivity values of 1.85x10-7 and 9.55x10-6 S cm-1 at 30 and 90 ºC, respectively. The lower values obtained for the other samples may be due to the appearance of aggregates, which corroborates with the XRD and SEM results. The new sample prepared with higher glycerol amount showed the highest conductivity values, namely 1.31x10-5 and 5.05x10-4 Scm-1 at 30 and 90 ºC respectively, so it was used to produce small electrochromic devices, which behaviour was evaluated.